2022
DOI: 10.1080/19490976.2022.2035658
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating live microbiota biobanking using an ex vivo microbiome assay and metaproteomics

Abstract: Biobanking of live microbiota is becoming indispensable for mechanistic and clinical investigations of drug–microbiome interactions and fecal microbiota transplantation. However, there is a lack of methods to rapidly and systematically evaluate whether the biobanked microbiota maintains their cultivability and functional activity. In this study, we use a rapid ex vivo microbiome assay and metaproteomics to evaluate the cultivability and the functional responses of biobanked microbiota to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Human stool samples were collected from healthy volunteers with a protocol approved by the Ottawa Health Science Network Research Ethics Board at the Ottawa Hospital (Ottawa, Canada). Protocols for stool collection, pre-processing, live microbiota bio-banking, and ex vivo microbiome culturing were described previously [4, 15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human stool samples were collected from healthy volunteers with a protocol approved by the Ottawa Health Science Network Research Ethics Board at the Ottawa Hospital (Ottawa, Canada). Protocols for stool collection, pre-processing, live microbiota bio-banking, and ex vivo microbiome culturing were described previously [4, 15].…”
Section: Methodsmentioning
confidence: 99%
“…Human stool samples were collected from healthy volunteers with a protocol approved by the Ottawa Health Science Network Research Ethics Board at the Ottawa Hospital (Ottawa, Canada). Protocols for stool collection, pre-processing, live microbiota bio-banking, and ex vivo microbiome culturing were described previously [4,15]. Protein extractions and trypsin digestion from microbiota and Caco-2 cells were performed using different protocols to demonstrate the wide applicability of the established dry TMT workflow.…”
Section: Sample Collection and Processing For Caco-2 Cells And Human ...mentioning
confidence: 99%
“…In the previous workflows, we described a 96-well based workflow to study the functional responses of individual gut microbiomes to xenobiotics in vitro. The development of the RapidAIM 2.0 protocol consists of three major parts, 1) optimized the culture medium and establishing and validating the 96-well based scalable culturing model [11,24]; 2) established a 96-well based metaproteomic sample processing and data analysis workflow [10]; and most recently, we 3) developed and validated a live microbiota biobanking workflow that is helpful to increase the reproducibility of experiments [23]. A limitation of the previous protocol was the considerably large sample size and LC-MS/MS time consumption for metaproteomics analysis.…”
Section: Development Of the Protocolmentioning
confidence: 99%
“…Either fresh human fecal samples or -80 o C stored biobank samples can be used for the culturing step. We previously showed that our culturing protocol maintains the functionality of individual microbiomes with both sample types [10,23]. Supplementary Methods 1 and 2 provide details for collecting and processing fresh stool samples, and collecting, processing and biobanking of the samples, respectively.…”
Section: As Illustrated Inmentioning
confidence: 99%
See 1 more Smart Citation